Positive and negative emotional responses to workrelated trauma of intensive care nurses in private health care facilities - Diane Elkonin; Lizelle Van der Vyver (AOSIS, 2011)
Intensive care nursing is a stressful occupation and nurses are continually subjected to both primary and secondary trauma. Responses may be positive in the form of compassion satisfaction, or negative in the form of compassion fatigue. However, nurses tend to deny the negative impact of secondary trauma which leads to the silencing response and subsequent burnout. This article explores and describes the presence of these emotions and the relationships between them. A quantitative approach with a non-probability sampling method was used. The sample consisted of 30 registered nurses working in private health care intensive care units in East London, Eastern Cape. Data were gathered via the Professional Quality of Life Scale: Compassion Satisfaction and Fatigue Subscales - Revision IV (ProQOL - R-IV) and the Silencing Response Scale and were analysed according to descriptive statistics and correlation coefficients. Findings suggest a high risk for compassion fatigue, a moderate risk for burnout and the silencing response and moderate potential for compassion satisfaction. A marked negative relationship was found between compassion satisfaction and burnout and a substantial positive relationship between compassion fatigue and burnout, as well as compassion fatigue and the silencing response. Opsomming Intensiewesorgverpleging is 'n stresvolle beroep en verpleegsters word gedurig aan beide primêre en sekondêre trauma blootgestel. Reaksie hierop kan óf positief wees, in die vorm van empatie-tevredenheid, óf negatief, in die vorm van empatie-uitputting. Verpleegsters is egter geneig om die negatiewe impak van sekondêre trauma te ontken,wat gevolglik tot stilswye en uitbranding kan lei. Hierdie artikel ondersoek en beskryf die teenwoordigheid en verwantskap tussen hierdie emosies. 'n Kwantitatiewe benadering met 'n nie-waarskynlikheidsteekproefmetode is gebruik. Die steekproef het bestaan uit 30 geregistreerde verpleegsters wat in privaat-intensiewesorgeenhede in Oos-Londen in die Oos-Kaap werk. Data is met behulp van die vierde hersiening van die 'Professional Quality of Life Scale: Compassion Satisfaction and Fatigue Subscales' en die 'Silencing Response Scale'ingevorder en verwerk met verwysing na beskrywende statistieke en korrelasiekoëffisiente. Die resultate dui op 'n hoë risiko vir empatie-uitputting, 'n matige risiko vir uitbranding en die stilswye-reaksie, sowel as 'n matige potensiaal vir empatie-tevredenheid. 'n Beduidende negatiewe verwantskap blyk tussen empatie-tevredenheid en uitbranding te bestaan, terwyl 'n aansienlik positiewe verwantskap tussen empatie-uitputting en uitbranding en empatieuitputting en die stilswye-reaksie bestaan.